FAKTOR RISIKO PENYEBAB TERJADINYA STUNTING PADA BALITA UMUR 12-59 BULAN DI KELURAHAN KAMPUNG BARU KEC. LUBUK BEGALUNG TAHUN 2015 - Erni Maywita (Akademi Keperawatan Kesdam I/Bukit Barisan Medan, 2018)
The prevalence of stunting in toddlers in Indonesia is still high, especially at the age 12 to 59 months.The aim of this research is to know the risk factor causes stunting to the toddlers who have the age 12 to 59 months in Kelurahan Kampung Baru Sub district of Lubuk Begalung Padang. The type of this research is observational with draft of case-control study. The dependent variable is the incidence of stunting in toddlers at the age 12 to 59 months. The sampling of case-control study is paired by ratio 1:1 with the number of samples 29:29. Univariate statistical test is using the distribution of frequency and also bivariate is using chi-square and multivariate. The result of this study is the toddlers who are not exclusively for getting ASI as much as 32% suffer from stunting. The toddlers who get poor parenting are 66.7% suffer from stunting, the toddlers who have families’ income are less well as much as 42.1% suffer from stunting, low mothers’ education level are 37.5% causes their toddlers suffer from stunting, the toddlers who have quantity of families more than 5 person are 52.4% suffer from stunting, the toddlers who have a history of infectious diseases are 62.9% suffer from stunting, the toddlers who suffer from ISPA in the last six months are 66.7% suffer from stunting, the toddlers who do not utilize Posyandu service are 60.9% suffer from stunting. There was a significant association of giving ASI (OR = 0,269), nutrition parenting (OR = 3.63%), a history of infectious diseases (OR 3.868) from stunting occurrence. There is no significant relationship between families’ income, mothers’ education level, quantity of families, Posyandu service utilization with the event of stunting. The dominant factor cause of stunting is parenting nutrition.It is important to increase education about nutrition to mothers by health workers so that awareness of mothers to improve the nutritional of toddlers is concerned about how to provide good parenting that can detect early occurrence of stunting in toddlers.Keywords: Stunting, giving breastfeeding, parenting, level of education, a history of infectious diseases, utilization of health service.